(untitled) (Fiep Bulletin - online, 2015)
The aim of this research is to analyze the course of former volleyball athletes who played for the Brazilian Volleyball Team during the 60, 70, 80 and 90 decades. We managed to unveil the prejudices and resistances concerning the practice of a competitive sport peformed by women in different generations, as well as in amateurism-professionalism fork, rebuilding stories about the women and the sports practices, so as to disclose the meaning of volleyball in their lives. The memory of the former athletes is the source of this research, and the theoretical- methodological reference is based upon the oral stories, providing a dialog between the official story and the way how these women featured and lived volleyball. Four women were interviewed during this study, they played for the Brazilian Volleyball Team in the midst of 1960 and 1990. The profile of women who were used to taking part in sport suffered transformations and the amateur ideal (recreational and educational) gave way to other interests such as, social rising and professional emancipation. Over the whole of their discourse, we have found out that these athletes had their lives linked to the sport, their experiences were all grounded around the depiction of a ball, and it was over it that they build their senses, sociability, friendships and passions. These outcomes have identified volleyball as the main point of these women lives, however, there is a difference related to their remaining in the sports career throghout the generations: i) the athletes from the 60s, when amateur volleyball was played, represented Brasil in competions only until their mariage dream came true. Ii) and, the ones who played after the 60s, broke up with amateur ideals and symbolized the women who had contraception and job rights (Lipovetsky, 2004). Being the latter, the ones who played untill their bodies could no longer bear the training programs, and ended up their careers at a ripe age.